FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PERMENDIKBUD NO.75 TAHUN 2016 DI SMK NEGERI BANJARMASIN - Syahrir Banjarmasin (DIA: Jurnal Administrasi Publik, 2019)
ABSTRACTOne example of the administration of education which involves the role and function of the School Committee can be observed in the city of Banjarmasin. Banjarmasin City Education Office seeks to change so that each school has facilities and infrastructure that can support teaching and learning activities outside of school through the School Committee. Good facilities and infrastructure facilities can support teaching and learning activities outside of school so that it is expected that each student can gain additional skills and knowledge from teaching and learning processes outside of school. Through community school committees can carry out various roles in the implementation and quality control of education services through the role of individuals, groups, families, professional organizations, employers, and social organizations. The study of strategies for developing community participation in education funding at State Vocational Schools in Banjarmasin as a result of the implementation of Permendikbud Nomor 75 Tahun 2016 and analyzing what factors make the implementation of Permendikbud Nomor 75 Tahun 2016 difficult to implement uses qualitative methods based on George C Edward's theory III produced findings that funding in schools that were previously with a collection system with the amount of payment that has been determined and agreed based on the school committee meeting, then with the implementation of the Permendikbud, it could no longer be done because the community meant that the contribution was voluntary, may contribute and may not. Based on these problems, the school is trying to find new breakthroughs to increase community participation in education funding to support funding in schools by developing Production Units (UP) and the community is expected to be directly involved in utilizing products produced by vocational students so that the problem of lack of funding at school can be overcome.